Diagnostic and Management Strategies of Aspergillus Endophthalmitis: Current Insights - Spadea L (Dove Medical Press, 2019)
Leopoldo Spadea, Maria Ilaria Giannico University “La Sapienza”, Department of Sense Organs, Eye Clinic, Rome, ItalyCorrespondence: Leopoldo SpadeaHead Eye Clinic, Policlinico Umberto 1, “Sapienza” University of Rome, Via Benozzo Gozzoli 34, Rome 00142, ItalyTel +39 06 519 3220Fax +39 06 8865 7818Email leopoldo.spadea@uniroma1.itAbstract: Fungal endophthalmitis is subsequent to endogenous or exogenous infection and represents an important complication of ocular surgery which may lead to significant visual loss and blindness. The prognosis is poor because of delayed diagnosis and limited availability of effective antifungal drugs with good ocular penetration. Furthermore, the critical issue in diagnosing fungal infection of the eye is microbiological identification of the etiologic agent in clinical samples. Aspergillus is among the most frequent isolated organisms in fungal endophthalmitis. Early diagnosis is essential to prevent severe complications and blindness. Treatments include local, systemic and surgical therapeutic strategies. The purpose of the present review is the analysis of the current procedures adopted to promptly diagnose and treat Aspergillus endophthalmitis.Keywords: Aspergillus, endophthalmitis, fungal infection, cataract surgery, ocular mycoses